NAMANGAN WÁLAYATÍ KENAGAS QARAQALPAQLARÍ - Prekeeva, A.A. (SCIENCE and SOCIETY, 2024)
This article is devoted to the issues of everyday life, history and dialect of the Karakalpaks living in the rural assembly of citizens «Kenagas» of the Pap district of the Namangan region.
Keywords: history of the Karakalpaks; Nogai Horde; Turkestan; nomadism; Khiva Khanate; Bukhara Emirate; Karakalpaks of the Kokand Khanate; Kenagas Karakalpaks; Kenagas tribe; Chyganak village; Syr Darya coast; isolated dialect